2023
DOI: 10.1155/2023/4113151
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lacrimal Punctum Position and Tear Meniscus Height after Correction of Horizontal Laxity in Involutional Lower Eyelid Entropion

Abstract: Purpose. To examine changes in the position of the lower eyelid punctum and tear meniscus height (TMH) after correction of horizontal laxity of the lower eyelid in involutional lower eyelid entropion. Methods. This prospective, observational study included 42 sides of 36 patients with involutional entropion who underwent a lateral tarsal strip procedure or transcanthal canthopexy (+ lower eyelid retractor advancement). The horizontal distance from the medial margin of the lower lacrimal punctum to the medial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In this study, the horizontal tightening of the eyelid tended to loosen slightly at 6 months postoperatively compared with the tightening effect at 3 months postoperatively. This trend is consistent with the results by Yokoyama et al, who examined the lateral shift in the position of the lacrimal punctum after horizontal eyelid-tightening surgery for lower eyelid entropion [ 12 ]. Their results indicated that the horizontal distance from the lower punctum to the medial canthus increased during the 3-month follow-up period, while at the 6-month follow-up, the distance decreased from the baseline measured at the 3-month follow-up but was still longer than that measured preoperatively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the horizontal tightening of the eyelid tended to loosen slightly at 6 months postoperatively compared with the tightening effect at 3 months postoperatively. This trend is consistent with the results by Yokoyama et al, who examined the lateral shift in the position of the lacrimal punctum after horizontal eyelid-tightening surgery for lower eyelid entropion [ 12 ]. Their results indicated that the horizontal distance from the lower punctum to the medial canthus increased during the 3-month follow-up period, while at the 6-month follow-up, the distance decreased from the baseline measured at the 3-month follow-up but was still longer than that measured preoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies [17][18][19][20] have investigated the grading method of MCT laxity. Te methods for measuring lacrimal punctum shift have been demonstrated [12,20]. However, the pinch test can directly assess horizontal eyelid laxity and is superior to these tests in ease of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Management of canalicular wall anomaly has been focused on alleviating symptoms by primarily treating associated lacrimal disorders [2]. A case of multiple canalicular wall hypoplasia with incomplete punctal canalization that underwent membranotomy had good functional and anatomical outcomes after a mean follow-up of 28 months [14]. The long duration of symptoms in all our patients and the decision of one to forgo surgery raise uncertainties on the severity of epiphora and the benefits and risks of intervention.…”
Section: Discussionmentioning
confidence: 98%
“…The use of AS-OCT to measure TMH provided quantitative data for further understanding the functional implications of the canalicular wall anomaly [ 12 ]. Singh et al [ 13 ] showed that TMH measured by OCT is statistically significant for a Munk severity grade of 2 and above.…”
Section: Discussionmentioning
confidence: 99%
“…The medial pretarsal adipose tissue in the lower eyelid was not examined in this study because it has not been found in the lower tarsus in most of the available research articles, although one publication suggested the presence of pretarsal adipose tissue in the lower eyelid. 9,10 In addition, because the lower eyelid retractors are fixed onto the lower edge of the lower tarsus rather than onto the tarsal surface during lower eyelid retractor advancement, 11 the pretarsal adipose tissue in the lower eyelid is less significant in the clinical setting.…”
Section: Methodsmentioning
confidence: 99%